2016
DOI: 10.1016/j.celrep.2016.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Prefrontal Neuron Activity Enables Associative Learning of Temporally Disparate Events

Abstract: The ability to link events that are separated in time is important for extracting meaning from experiences and guiding behavior in the future. This ability likely requires the brain to continue representing events even after they have passed, a process that may involve the prefrontal cortex and takes the form of sustained, event-specific neuron activity. Here, we show that experimentally increasing the activity of excitatory neurons in the medial prefrontal cortex (mPFC) enables rats to associate two stimuli s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 49 publications
(57 reference statements)
3
28
0
Order By: Relevance
“…Among the 19 rats included in the behavioral analysis, 10 rats were used for the analysis of c-Fos expression. In addition to the 24 rats that were purchased for this study, we reanalyzed c-Fos expression data collected from 15 rats in our previous study (Volle et al, 2016). All procedures were in accordance with the National Institutes of Health Guide for the Care and Use of Laboratory Animals (Publication No.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 19 rats included in the behavioral analysis, 10 rats were used for the analysis of c-Fos expression. In addition to the 24 rats that were purchased for this study, we reanalyzed c-Fos expression data collected from 15 rats in our previous study (Volle et al, 2016). All procedures were in accordance with the National Institutes of Health Guide for the Care and Use of Laboratory Animals (Publication No.…”
Section: Methodsmentioning
confidence: 99%
“…All analyses were performed using custom code written in MATLAB (MathWorks) with the same procedure as that used in our previous studies (Volle et al, 2016; Morrissey et al, 2017). For each session per animal, the amplitude of the EMG signal during each 1 ms of time was calculated by subtracting the minimum signal from the maximum signal during that 1 ms window.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, one hour after training in contextual fear conditioning, the transcription of multiple plasticity-related genes is upregulated in the mPFC, leading to immediate changes in synaptic structure and physiology (Bero et al, 2014). Parallel studies also showed that by enhancing the activity of mPFC neurons during training, it is possible to facilitate the acquisition of hippocampusdependent memories (Benn et al, 2016;Volle et al, 2016;Jarovi et al, 2018;Shibano et al, 2020). These observations, along with earlier findings of impaired hippocampus-dependent memories with disrupted mPFC (Hannesson et al, 2004;Takehara-Nishiuchi et al, 2005;Zhao et al, 2005;Barker and Warburton, 2008;Gilmartin and Helmstetter, 2010;Devito and Eichenbaum, 2011;Gilmartin et al, 2013;Bero et al, 2014), led us to hypothesize that the mPFC may work with, but not follows, the hippocampus to form new memories (Takehara-Nishiuchi, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, numerous studies have shown in various animal models that higher neuronal activity at the time of learning facilitates memory formation (Saar et al, 1998; Stackman et al, 2002; Zelcer et al, 2006; Han et al, 2009; Santini and Porter, 2010; Santini et al, 2012; Volle et al, 2016). This discrepancy may in part be because LTM formation in this paradigm is induced by inhibitory inputs, elicited by the conditioning stimuli, to the RPeD1.…”
Section: Discussionmentioning
confidence: 99%